Localized scleroderma - current treatment options - Katarzyna Wolska-Gawron; Małgorzata Michalska-Jakubus; Dorota Krasowska (Termedia Publishing House, 2017)
Localized scleroderma (morphea) is a connective tissue disease that affects the skin, subcutaneous tissue and underlying tissues including the fasciae, muscles and bones. The treatment of localized scleroderma depends on the clinical form of the disease, its severity/activity, extent of skin lesions and patient's age. Patients with limited skin involvement caused by morphea require topical therapy with glucocorticoids, calcineurin inhibitors, calcipotriol or UVA/PUVA phototherapy. More severe variants of localized scleroderma with extensive tissue involvement require immediate systemic therapy with glucocorticoids and/or methotrexate, or mycophenolate mofetil. According to recent reports, attempts have also been taken, with variable clinical outcomes, to treat localized scleroderma topically with pirfenidone and imiquimod, systemically with tacrolimus and cyclosporine; and with fractional CO 2 laser, photodynamic therapy and autologous fat transfer. The article presents current therapeutic methods of localized scleroderma.